Master's thesis of Tianshi Zhang - Zhang, Tianshi (My University, 2016)
Novel electrocchemical and chemical strategies have been developed for the fabrication of functional nanocomposites. New scientific and engineering contribution of this work to colloidal nanotechnology included the development of advanced chelating dispersing agents, such as various small organic molecules and chelating polymers. The unique feature of such dispersion agents is their strong adsorption on the surface of different materials, which allows superior dispersion. The chelating monomers of chelating polymers, such as PAZO and PMSS provided multiple adsorption sites for bonding to metal atoms on the particles surface. We analyzed and developed new fundamental adsorption and dispersion mechanisms. An important finding was the possibility of co-dispersion and co-deposition of advanced materials such as oxides, nitrides, complex oxides and minerals using universal dispersing agents and formation of composites by EPD method. It was found that Caffeic acid (CA) can be used as an efficient dispersing agent for the synthesis of ZnO nanorods of reduced size and a dispersing agent for the EPD of ZnO films. Another important achievement of this work was the application of tannic acid as an efficient capping and dispersing agent for synthesis and EPD of inorganic materials and composites. An important discovery was the use of lauryl gallate dispersant as a reducing agent for the synthesis of AgNp and a vehicle for particle dispersion and extraction in the liquid-liquid extraction method. Further advancements in our new technologies allowed us to develop composite films using anodic EPD using weak polyelectrolytes, such as alginate. The composite coatings exhibited protective and flame retardant properties. We analyzed the deposition mechanisms and kinetics as well as microstructure of the coatings. In another strategy, we developed electrochemical strategies for the deposition of composites, based on strong polyelectrolytes. The approach is based on the EPD of the polyelectrolyte molecules and electrosynthesis of EPD of ceramic particles. The electrostatic heterocoagulation mechanism was proposed for the deposit formation. We investigated the deposition kinetics, composition and microstructure of the composites prepared by the new strategies. The new electrochemical strategies can be used for the deposition of other composites, based on functional polymers with pH independent charge. New methods have been developed for the chemical synthesis of PPy based composites, using PMSS, PMSS–SR11 and PMSS–SR31 as anionic dopants for chemical polymerization and dispersants for MWCNT. The composites showed promising performance for application in electrodes of electrochemical supercapacitors. Good electrochemical performance was achieved at high active mass loadings. The electrodes showed high capacitance, large voltage window and low impedance. The analysis of electrochemical testing results and chemical structure of PMSS, PMSS–SR11 and PMSS–SR31 provided an insight into the influence of the anionic functional groups on the capacitance and capacitance retention a high charge-discharge rates.
Electrochemical and Chemical Methods for the Fabrication of Nanocomposites
Keywords: Master's thesis; Nanocomposites; Electrodeoposition; Dispersants